Economic and Systemic Consequences of Adaptation to External and Internal Pressures Caused by Global Crisis in China - Mária Csanádi (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2012)
Global downturn in 2008 exerted strong adaptation pressures on China that incited prompt state response. The one-off large state intervention had consequences in several dimensions: on the one hand, it had a positive impact on the system's short-term economic, social and political stability by dynamizing different economic sub-spheres. State intervention, at the same time, temporary slowed down the process of economic transformation and also mobilized system characteristics that lead to overheating and to renewed state intervention to cool it down. This paper sheds light on the consequences of adaptation to external and internal pressures on national, sectoral, regional, and structural dimensions from a systemic point of view.
Keywords: F5; D78; R58; J08; O15; E24; 330; party-state model; short-term shocks; adaptation; system transformation; global crisis; overheating; spatial disparities; Wirtschaftskrise; International; Wirkungsanalyse; Systemtransformation; Räumliche Verteilung; China